Transversus Abdominis Plane (TAP) Block for Postoperative Analgesia in Acute Pulmonary Oedema Following Caesarean Section- A Case Report (Journal of Armed Forces Medical College, Bangladesh, 2015)
A thirty six years old woman admitted in ICU following emergency lower uterine caesarean section under subarachnoid block (SAB). After 03 hours of surgical procedure, the patient develops severe respiratory distress. Patient was evaluated and diagnosed as a case of acute pulmonary oedema. In ICU, she was aggressively treated with intravenous Morphine, frusemideand parenteral antibiotic. After 1 hour of intensive care management, respiratory distress decreased but not significantly, in addition, she complains of severe pain on surgical operative site. Post operative analgesia was maintained with parectamol (500 mg) suppositories six hourly and intramuscular pathedine 75 mg 8 hourly. Instead of this her pain scores were 7/10 at rest and 8/10 on coughing along with respiratory distress. Then in ICU under all aseptic precaution bilateral TAP block was performed using landmark technique with 0.25% plain bupivacine 20 ml. Thirty minutes later, her pain subsided significantly and pain score became 1/10 at rest and 2/10 on coughing. Thereafter patient was slept for 4 hours, pain free and could take care of herself. After 48 hours patient was shifted to ward and discharged on 7th post operative day. TAP block is relatively easy, safe techniques. Because of simplicity and low cost, TAP block is likely to be an effective adjunct to multimodal postoperative analgesia for abdominal surgery.Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014